2013
DOI: 10.3855/jidc.2486
|View full text |Cite
|
Sign up to set email alerts
|

Ugandan medical and health sciences interns’ infection control knowledge and practices

Abstract: We assessed the level of knowledge, attitudes, and practices of recent graduates of clinical health sciences who started their one-year internship in Uganda. Methodology: This was a cross-sectional survey responded to by 209 (response rate of 70%) new interns who started their internships in August 2011 in different Ugandan hospitals. Validated self-administered questionnaires with knowledge, attitude, and practices questions were distributed to the participants during a two-day internship orientation organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
3
12
2
Order By: Relevance
“…However, the findings on H1 were consistent with studies (e.g., Rusnah et al, 2009;Chen & Chen, 2011) that did not find cognitive learning experience to be a correlate of internship. The findings on H2 also joined the category of earlier studies that did not find a correlation between behavioral learning experience and internship, study (e.g., Chen & Chen, 2011) yet the findings on H3 were also consistent with findings of studies (e.g., Rusnah et al, 2009;Kamulegeya et al, 2012) that did not find a correlation between environmental learning experience and Internship.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the findings on H1 were consistent with studies (e.g., Rusnah et al, 2009;Chen & Chen, 2011) that did not find cognitive learning experience to be a correlate of internship. The findings on H2 also joined the category of earlier studies that did not find a correlation between behavioral learning experience and internship, study (e.g., Chen & Chen, 2011) yet the findings on H3 were also consistent with findings of studies (e.g., Rusnah et al, 2009;Kamulegeya et al, 2012) that did not find a correlation between environmental learning experience and Internship.…”
Section: Discussionsupporting
confidence: 80%
“…However, some studies found environmental learning to be a negative correlate of internship. For example, Rusnah et al (2009) which looked into undergraduate internship attachment in accounting and Kamulegeya, Kizito et al (2012) which addressed the Ugandan medical and health science interns' infection knowledge and practice. The controversy in findings warrants further investigation to be done on the hypothesis to the effect that:…”
Section: Environmental Learning As a Covariate Of Internshipmentioning
confidence: 99%
See 1 more Smart Citation
“…This is found to be less than other studies, that had (75.5%) of respondents that reported to adhere to wearing gloves while performing procedures (11). A study in Uganda had (83.25%) of the respondents who always use gloves when drawing blood or placing cannulas (14). On the other hand, a study done on Healthcare workers had lesser results than ours, where only (43%) have always used gloves when drawing blood (15).…”
Section: Discussion:-contrasting
confidence: 52%
“…In contrast, Abdullahi and colleagues [11] showed that 26.5% of nurses out of 518 subjects had very low level of knowledge with respect to infection control measures [11]. Kamulegeya et al [12] also found that 51.4% of nurses out of 209 participants have poor or wrong knowledge about the transmission of blood-borne organisms [12]. In the study by Darawad and colleagues [13] which evaluated 198 nurses, it was also shown that Jordanian nurses have moderate level of compliance with hand-washing and poor knowledge about hand hygiene protocols [13].…”
Section: Discussionmentioning
confidence: 99%